THE PENGARUH TINGKAT PENDIDIKAN TERHADAP PENINGKATAN KINERJA PEGAWAI PADA BADAN KESATUAN BANGSA DAN POLITIK PROVINSI SULAWESI SELATAN - Maulana Muhammad; Jessica F. Tonapa (Jurnal Administrasi Negara, 2021)
The achievement of the employee performances of the National and Political Unity Agency of South Sulawesi Province in the last 3 years shows a percentage that is not very stable where the educational level factor of the various staffs needs to be considered. In 2017 and 2018 the percentage of performance achievements was categorized quite high, while in 2019 it was in the medium category. The objective of this study was to determine the influence of educational level on improving employee performance. This study used a quantitative type with associative research type to determine the effect between two variables. Data were collected through questionnaires, observation and documentation. The sample of this study was the entire study population that consist of 48 people with a saturated sampling technique. The technique of data analysis applied simple linear regression analysis, pre-test requirements analysis and hypothesis testing. The results showed that the level of education had a positive and significant effect on improving employee performance with a percentage of 24%. The Intellectual skills obtained from the education level should be accompanied by other efforts such as competency development in supporting performance improvement.